THE ENFORCEMENT OF CRIMINAL LAW AGAINST VIOLENT THEFT CRIMES - Mabsuti, Mabsuti; Fitnawati WN, Santy (JURNAL RUANG HUKUM, 2023)
Occasionally, technological advancements and the growth of human civilization are accompanied by an increase in human requirements. This has a negative effect because it will increase the likelihood of criminal activity. Theft with violence is a type of crime that has recently occurred in every region and has been extensively discussed, as it severely disrupts security and public order. Consequently, the purpose of this study was to investigate the enforcement of criminal law against the offense of larceny with violence. Using a normative juridical approach with a statutory approach and a case approach, secondary data with additional primary, secondary, and tertiary legal materials were analyzed qualitatively in this study. In light of these findings, Chapter XXII of the Criminal Act of Theft is governed by Articles 363, 363, and 365 of the Criminal Code (KUHP). This indicates that law enforcement officials must refer to these articles when imposing violent punishments on thieves. Violent crime Criminal law enforcement is an effort to translate concepts of criminal law justice into legal certainty and social benefits in every legal relationship. There are three factors that must always be considered in law enforcement: 1) legal certainty (Gerechtigkeit), 2) justice, and 3) effectiveness. Legal structure, legal substance, legal culture, and legal remedies (preventive and punitive measures) comprise the efforts to uphold the law in instances of theft crimes involving violence.